Hubungan Religiusitas dengan Kontrol Diri dalam Penggunaan TikTok pada Remaja - Aulia, Wina; Maputra, Yantri; Afriyeni, Nelia; Sari, Liliyana (Jurnal Psikologi Udayana, 2022)
The use of the TikTok is currently dominated by adolescents. Adolescents attempt to look as attractive as possible in TikTok without even considering the negative consequences of their actions. Self-control of adolescents can minimize the negative impacts of using TikTok. Self-control in using TikTok among adolescents can be obtained from guidelines in the form of values, one of which is the value of religion or religiosity. This study aimed to examine the relationship between religiosity and self-control in using TikTok among adolescents. The method used in this study was quantitative with 150 subjects aged 11-17 years who uploaded videos on TikTok. The instruments were the Self-Control in Using TikTok Scale and the Centrality of Religiosity Scale (CRS-15). The Spearman's Rank correlation test results showed that there was a positive relationship between religiosity and self-control in using TikTok for adolescents (r=0.162; p=0.048). The results indicated that higher religiosity is associated with higher self-control in using TikTok among adolescents, and the lower the religiosity, the lower the self-control in the use of TikTok in adolescents. In addition, most adolescents in the study were reported to have a high level of religiosity whereas moderate level of self-control in the use of Tiktok.